The effects of short-term intake of dietary zinc nanoparticles on plasma mineral and antioxidant status, nutrient digestibility, and intestinal microbiota in lambs - Čobanová, Klaudia; Bujňáková, Dobroslava; Bombárová, Alexandra; Kucková, Katarína; Grešáková, Ľubomíra; Váradyová, Zora; Kopel, Pavel (Frontiers in Veterinary Science, 2026)
This study was conducted to evaluate the impact of short-term dietary supplementation with different zinc nanoparticles (Zn NPs) on plasma mineral status, antioxidant response, hematological parameters, apparent nutrient digestibility, intestinal microbial population and bacterial enzymatic activity in growing lambs. Twenty-seven male lambs (Improved Valachian, initial weight 21.2 ± 1.1 kg) aged 5 months were randomly assigned to one of three treatments (n = 9) for 28 days. Each group was fed the identical basal diet with either no supplemental Zn (control group, CON) or supplemented with commercial ZnO nanoparticles (ZnO NPs) or synthesized zinc phosphate nanoparticles (ZnP NPs) at the same dose of 80 mg Zn/kg diet. The results showed that the dietary treatment had no significant effects on the hematological and selected biochemical parameters, plasma metalloprotein level and apparent nutrient digestibility. On day 14, intake of ZnP NPs significantly elevated Zn (p < 0.01) and Fe concentration (p < 0.05) in plasma compared to the CON and ZnO NPs groups. Regardless of the source, supplementation with Zn NPs increased plasma total antioxidant status on day 28 compared to the CON group (p < 0.01), but it did not affect the lipid peroxidation in plasma and activity of antioxidant enzymes in blood. The intake of Zn NPs significantly influenced fecal microbial communities; specifically, reduced populations within the Ruminococcus-Eubacterium-Clostridium cluster and/or the Bacteroides/Prevotella group were observed compared to the CON group, especially at the end of the experiment (p < 0.001). Furthermore, the activity of bacterial enzymes, such as β-glucuronidase, N-acetyl-glucosaminidase and β-galactosidase, was significantly decreased during the experiment in both groups receiving Zn NPs. In conclusion, short-term feeding of diets supplemented with different Zn NPs at 80 mg Zn/kg diet improved total antioxidant status in plasma and did not induce oxidative stress in growing lambs. Dietary Zn NPs were also found to be very effective in altering gut microbiota composition and inhibiting bacterial enzyme activity.